A 10-year-old Boy with Giant Choledochal Cyst: A Case Report - Ninung RD Kusumawati; Juwita Pratiwi (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Choledochal duct cyst is a rare congenital anomaly in the form of cystic dilatation of both intrahepatic and extrahepatic bile ducts. The clinical symptoms of choledochal cysts are generally due to bile stasis, stone formation, recurrent superinfection, and inflammation. This case depicts a 10-year-old boy presented with a chief complaint of an enlarged abdomen that was rapidly growing, sub-febrile fever and yellowing of the sclera. A choledochal duct cyst was shown in the abdominal ultrasonography. Laboratory examination showed an increase in liver function test, hypoalbuminemia, and prolonged coagulation profile. Magnetic resonance cholangiopancreatography showed a significant cystic dilatation of the common bile duct extending to the common hepatic duct. Surgery was performed twice, first to drain the cyst and second to perform complete excision and anastomoses to the jejunum, as fluid continued to refill the cyst.